Trends in the use of postprostatectomy therapies for patients with prostate cancer: A Surveillance, Epidemiology, and End Results Medicare analysis. Issue 18 (10th July 2013) - Sheets, Nathan C.; Hendrix, Laura H.; Allen, Ian M.; Chen, Ronald C.
<x xml:space="preserve">Abstract</x> BACKGROUND For patients with adverse pathologic factors (positive surgical margins, extracapsular extension, or seminal vesicle invasion) on prostatectomy pathology, the use and timing of postsurgical treatments are controversial. The goal of the current study was to examine patterns of care in patients with a pathologic indication for postprostatectomy radiotherapy (RT) using the Surveillance, Epidemiology, and End Results (SEER)‐Medicare–linked database. METHODS A total of 3460 men treated with radical prostatectomy for localized prostate cancer between 2000 and 2006 with at least 1 adverse pathologic factor and at least 3 years of claims data after surgery were included. Medicare claims through December 31, 2009 were examined. Rates of postprostatectomy hormonal therapy, RT, or both were examined. Logistic regression analysis examined potential factors associated with the receipt and timing of RT. RESULTS Within 3 years after surgery, 1076 patients (31%) received some form of further therapy, including 850 (25%) who received RT. Receipt of RT was < 35% in all subgroups including every year of study. Fewer than one‐half of patients who received RT (43%) did so within 6 months of surgery. On multivariate analysis, pathologic T classification and tumor grade were associated with receipt of RT within 6 months or 3 years of surgery, as were younger age, geographic region, and population density. CONCLUSIONS Rates of postprostatectomy RT remain low and the timing of RT has not appreciably changed since the publication of the randomized trials supporting the use of adjuvant RT. The use of hormone therapy is almost as common as RT, despite a relative lack of evidence supporting its use in this setting. Cancer 2013;119:3295–301. © 2013 American Cancer Society.